THE ROLE OF DANCE AND MUSIC IN AESTHETIC EDUCATION (The Conference Hub, 2025)
Dance and music are among the most universal forms of human expression, and their significance in the field of education extends far beyond entertainment. This thesis examines the role of dance and music in shaping aesthetic awareness, emotional intelligence, creativity, and cultural identity. The research analyzes the pedagogical value of integrating these art forms into educational systems, showing how rhythm, movement, and musical harmony stimulate intellectual and emotional development in children and young people. Comparative examples from European, Asian, and Latin American educational models highlight how dance and music contribute to holistic personal growth and intercultural understanding. The findings affirm that dance and music should be regarded as essential elements of aesthetic education in the 21st century.